2014
DOI: 10.1007/s40670-014-0019-0
|View full text |Cite
|
Sign up to set email alerts
|

Interest and Involvement in Research During Medical School: a Global Comparison of Students at High- and Low-Income Universities

Abstract: Objectives The objective of this study is to explore the attitudes, involvement, and knowledge of international medical students regarding research, as well as the barriers they face. Methods This is a cross-sectional survey that involves a selfadministered anonymous questionnaire with international medical students. Results A total of 221 adequately filled surveys were returned, 128 from high-income and 93 from low-and middle-income countries. Even though about 70 % of students were interested in research, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…In the present study, it was evident that medical students were not completely research-naïve, with 44.3% reporting previous engagement in projects leading to notable academic outputs. While one international study has previously reported broadly similar levels of research engagement [ 7 ], these figures contrast with lower rates reported across one UK medical school [ 5 ], where only 38% final-year students described previous research participation, with fewer than three quarters achieving any academic output. One explanation for this may be the aforementioned general growth in academic activity in recent years.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In the present study, it was evident that medical students were not completely research-naïve, with 44.3% reporting previous engagement in projects leading to notable academic outputs. While one international study has previously reported broadly similar levels of research engagement [ 7 ], these figures contrast with lower rates reported across one UK medical school [ 5 ], where only 38% final-year students described previous research participation, with fewer than three quarters achieving any academic output. One explanation for this may be the aforementioned general growth in academic activity in recent years.…”
Section: Discussioncontrasting
confidence: 59%
“…Such expectations are similar in other European countries such as Germany, where a period of formal undergraduate research and resulting thesis submission is mandatory prior to assuming the title of ‘Doctor’ [ 3 ]. However, numerous practical, cultural and political barriers restrict medical students’ participation in high quality audit and research projects, including a perceived lack of time and opportunity, hostile environments and inadequate academic training in medical school [ 4 - 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current literature has identified several practical barriers that prevent medical students from doing so, including lack of opportunity, hostile hospital culture and insufficient base knowledge. 9–11 Students are often unsure of how to contact a potential supervisor for an audit, due to fear of rejection. The finding of audit projects with supervisors working in a speciality of interest is usually down to chance.…”
Section: Introductionmentioning
confidence: 99%
“…Using World Bank definitions of countries' incomes, we noted that there were fewer selected studies from medical schools in lower-middle-and low-income countries, where student involvement in original research may not be the priority to address local healthcare needs in these curricula. However, a paper by Salloum et al found that there appeared to be the same appetite in medical students to do research from high and lower income countries [56].…”
Section: Key Findingsmentioning
confidence: 99%